2012
DOI: 10.5005/jp-journals-10005-1150
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Association between Oral Health Status and School Performance? A Preliminary Study

Abstract: The present cross-sectional study was carried out to assess the impact of poor oral health status on school performance of 600 primary and nursery school children of Bengaluru city, India. The data were collected using the methods and standards recommended by the WHO for oral health surveys. Oral health status was assessed using the df-t index (number of decayed and filled teeth). Academic performance was assessed based on the marks obtained. The children were divided into three groups: Excellent, average, bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…Yet the literature is still unclear regarding the impact of oral conditions on school performance. Some studies found a significant association between cavitated dentin lesions and academic performance while others did not . In this study, the results indicated a significant association between school performance and the final CPQ score, which subjectively evaluates the impact of oral health on a child's daily activities.…”
Section: Discussionmentioning
confidence: 49%
“…Yet the literature is still unclear regarding the impact of oral conditions on school performance. Some studies found a significant association between cavitated dentin lesions and academic performance while others did not . In this study, the results indicated a significant association between school performance and the final CPQ score, which subjectively evaluates the impact of oral health on a child's daily activities.…”
Section: Discussionmentioning
confidence: 49%
“…Most studies were conducted in schools, and the sample sizes varied between 312 and 65 680 participants . Dental caries was the most investigated dental exposure as it was assessed in nine studies . The DMFT and ICDAS were the predominant clinical indices employed to evaluate dental caries.…”
Section: Resultsmentioning
confidence: 99%
“…Parent's perception of child's oral health was investigated in six studies, while three studies investigated self‐perceived oral health and other three studies assessed toothache . Of the 12 studies on school performance, eight used information from school registers, and nearly three of the studies on school attendance obtained information from school reports …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The psychosocial impact of oral diseases often significantly diminishes quality of life and children are the worst affected group. [3] Children are more prone to numerous oral conditions that may have a negative impact on quality of life which may be quantified in terms of dropping out from school; disruption to physical activity, eating, sleeping, and studying, which may affect their emotions adversely. The gravity of the situation further deepens when we talk in terms of oral health conditions of differently abled children.…”
Section: Introductionmentioning
confidence: 99%